OP0053 Inflammatory disorders associated with trisomy 8 myelodysplastic syndromes : french retrospective case control study. (12th June 2018) - Wesner, N.; Drevon, L.; Guedon, A.; Fraison, J.B.; Trad, S.; Kahn, J.E.; Aouba, A.; Gillard, J.; Ponsoye, M.; Hanslik, T.; Gourguechon, C.; Liozon, E.; et al.
Abstract : Objectives: We report myelodysplastic syndrome (MDS)-associated systemic inflammatory and autoimmune diseases (IADs) with cytogenetic trisomy 8, and describe their outcome, treatments efficacy and impact on MDS survival in a French multicenter retrospective study. Methods: In this study, 21 patients with trisomy 8-MDS and IADs were analysed and compared to 103 MDS patients with trisomy 8 without IADs. Results: The median age was 67 [59 – 80] years and the male/female ratio 0.9. The IADs were Behçet's or Behçet's-like disease in 11 (52%) cases, inflammatory arthritis in 4 (19%) cases, Sjögren's syndrome, autoimmune hemolytic anaemia, aseptic abscesses, polyarterits nodosa, Sweet's syndrome and unclassified vasculitis in one case each. Trisomy 8 karyotype was isolated in 8 cases (38%) and associated with other abnormalities in remaining cases. Seventeen (81%) IADs patients were treated (88% with steroids) with complete and partial response in 35% and 47%, respectively. A second-line therapy was required for steroid dependence or relapse in 38% of cases. The effect of MDS treatment on IADs could be assessed in 7 patients treated with Azacytidine : 5/13 (38%) achieved remission and 2/13 (15%) partial response of IADs. Compared with 103 trisomy 8-MDS/CMML patients without IADs, IADs patients were more often non-Caucasian (p=0.004), MDS subtype tended to be more frequently CRDM (p=0.09) and had more often a poor karyotype (p<0.001). No survival difference was seen between patients with trisomy 8-MDS-associated IADs and without IADs. Conclusions: The spectrum of IADs associated to trisomy 8-MDS is dominated by Behçet's disease, but may also be other various immune disorders. Steroid therapy is often effective, but sparing therapies are mostly necessary. Disclosure of Interest: None declared